Is 3 the new 1: perspectives on virology, natural history and treatment for hepatitis C genotype 3. Issue 10 (8th September 2013) - Tapper, E. B.; Afdhal, N. H.
Summary: Affecting 2–3% of the world's population, hepatitis C is a common viral infection which is a significant cause of morbidity and mortality. Hepatitis C genotype 1 is the dominant viral genotype among Western patients. For the last 20 years, in the era of interferon‐based therapy, it was far more difficult to treat relative to genotypes 2 and 3. Accordingly, a significant focus of research was on new antiviral agents for the dominant genotype 1 patient. Now, as promising specific treatments are being introduced for genotype 1, the attention of clinicians and researchers has turned back to the 50–70 million patients infected with a nongenotype 1 hepatitis C. Furthermore, after recent, larger randomized trials, we have realized that genotype 2 is truly interferon sensitive while genotype 3 patients are far less successful with therapy. In this fundamentally altered landscape, genotype 3 is now potentially the most difficult to treat genotype and an area of intense research for new drug development. Herein we review the virology, natural history and the treatment of genotype 3 hepatitis C.